The alluvial architecture of a suspended sediment dominated meandering river: the Río Bermejo, Argentina - Sambrook Smith, Gregory H. (2016)
The alluvial architecture of fine-grained (silt-bed) meandering rivers remainspoorly understood in comparison to the extensive study given to sand-bed andgravel-bed channels. This paucity of knowledge stems, in part, from the difficultyof studying such modern rivers and deriving analogue information fromwhich to inform facies models for ancient sediments. This paper employs anew technique, the parametric echosounder, to quantify the subsurface structureof the Rıo Bermejo, Argentina, which is a predominantly silt-bed river witha large suspended sediment load. These results show that the parametricechosounder can provide high-resolution (decimetre) subsurface imaging fromfine-grained rivers that is equivalent to the more commonly used ground-penetratingradar that has been shown to work well in coarser-grained rivers. Analysisof the data reveals that the alluvial architecture of the Rıo Bermejo ischaracterized by large-scale inclined heterolithic stratification generated bypoint-bar evolution, and associated large-scale scour surfaces that result fromchannel migration. The small-scale and medium-scale structure of the sedimentaryarchitecture is generated by vertical accretion deposits, bed sets associatedwith small bars, dunes and climbing ripples and the cut and fill fromsmall cross-bar channels. This style of alluvial architecture is very differentfrom other modern fine-grained rivers reported in the literature that emphasizethe presence of oblique accretion. The Rıo Bermejo differs from these other riversbecause it is much more active, with very high rates of bank erosion andchannel migration. Modern examples of this type of highly active fine-grainedriver have been reported rarely in the literature, although ancient examples aremore prevalent and show similarities with the alluvial architecture of the RıoBermejo, which thus represents a useful analogue for their identification andinterpretation. Although the full spectrum of the sedimentology of fine-grainedrivers has yet to be revealed, meandering rivers dominated by lateral or obliqueaccretion probably represent end members of such channels, with the specificstyle of sedimentation being controlled by grain size and sediment load characteristics.